Which patients with syncope should be admitted to the hospital?. Issue 6 (June 2016) - Kim, William; Lyon, Corey
Abstract : Case : A 62‐year‐old man with a history of CHF (LVEF=40%), diabetes, and hypertension presents with a first‐time episode of syncope. He describes a feeling of warmth upon standing from the bed, lightheadedness, and then passing out. Previously his chronic medical conditions had been stable. He has been adherent to his medications. Initial evaluation revealed a normal ECG, no concomitant trauma, and a normal neurological examination. Should this patient be admitted to the hospital?